Christian Nurture of Children in the Writings of Horace Bushnell and Ellen G. White. Issue 2 (3rd May 2016) - Jankiewicz, Darius; Jankiewicz, Edyta
ABSTRACT: Until the 20th century, the spiritual nurture of children was not a high priority for the Christian church. In fact, for most of Christian history, reflection on the nature of children and their faith formation was often considered "beneath" the work of theologians. Two 19th-century American Christian writers, however, stand in sharp contrast to this trend: Horace Bushnell (1802–1876) and Ellen G. White (1827–1915 ). This article examines, compares, and contrasts the thoughts of these two thinkers on Christian nurture within the context of their lives and theologies of human nature and salvation.